Maternal glucose in pregnancy is associated with child's adiposity and leptin at 5 years of age. Issue 9 (16th March 2021) - Blais, Kasandra; Arguin, Mélina; Allard, Catherine; Doyon, Myriam; Dolinsky, Vernon W.; Bouchard, Luigi; Hivert, Marie‐France; Perron, Patrice
Summary: Background: Exposure to maternal hyperglycaemia in pregnancy has been associated with childhood obesity. Leptin regulation might be involved in this 'adiposity programming' and may depend on timing of exposure. Objectives: To investigate associations of maternal glycaemia at different periods in pregnancy with childhood adiposity and leptin levels at 5 years of age. Methods: In a prospective pre‐birth cohort, we measured maternal glucose levels after a 50 g oral glucose challenge test at first trimester (9.8 ± 2.3 weeks) and during a 75 g oral glucose tolerance test at second trimester (26.5 ± 0.9 weeks). We followed up children at 5 years; we measured anthropometry and body composition using dual‐energy X‐ray absorptiometry (DXA). We measured fasting leptin levels using immunoassays (Luminex) in 328 children. We conducted linear regression analyses, adjusting for potential confounders. Results: Maternal glycaemia at first trimester was associated with childhood leptin levels at 5 years, independently of maternal pre‐pregnancy BMI and other confounders ( β  = .09 ± .04; P  = .03). Higher post‐load glucose levels at second trimester were associated with greater total body fat percentage measured by DXA (1 hour‐glucose: β  = .010 ± .004; P  = .03 and 2 hours‐glucose: β  = .016 ± .005; P  = .002), but not with leptin levels. Conclusions: Our results suggest that programming of leptin regulation may be sensitive to maternal hyperglycaemia specifically in early pregnancy.